Pengembangan Produk dan Strategi Pemasaran pada Penjualan Produk Umkm Kebab Cake : (Studi Kasus di Warung Kebab By Al-Barra Kota Binjai) - Juan Charmel Askelon Siregar; Nurul Wardani Lubis; Riris Amigo Simatupang; Gaby P F Tampubolon; Reyka Triana Yohana Sidabatur (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study examines the product development and marketing strategies of the Kebab Cake By Al-Barra in Binjai City, aiming to increase consumer interest and sales. Warung Kebab By Al-Barra, established in 2021, initially sold regular kebabs before innovating with the kebab cake product, which is more appealing to consumers compared to traditional sweet cakes. In addition to kebab cakes, other products such as kebab box packages and kebab pizza were also developed. The marketing strategies implemented include sales through physical stores and digital marketing via social media and food delivery applications. Furthermore, attractive product design, discount promotions, and quality control are integral parts of their marketing strategy. The research results show that these product innovations and marketing strategies are effective in increasing interest and sales, making the kebab cake a popular product in Binjai City and providing an important example for other in facing intense competition.